2002
DOI: 10.1046/j.1365-2427.2002.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the bacterial response to spectral solar radiation by algae and limiting nutrients

Abstract: SUMMARY 1. The response of bacterial production (measured as [3H]TdR incorporation rate) to spectral solar radiation was quantified experimentally in an oligotrophic high‐mountain lake over 2 years. Bacterial responses were consistent: ultraviolet‐B (UVB) was harmful, whereas ultraviolet‐A (UVA) + photosynthetically active radiation (PAR) and PAR enhanced bacterial activity. Full sunlight exerted a net stimulatory effect on bacterial activity in mid‐summer but a net inhibitory effect towards the end of the ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 75 publications
(107 reference statements)
7
53
2
Order By: Relevance
“…This ecosystem experiences frequent inputs of atmospheric Saharan dust containing high P levels, with a mean molar TN : TP ratio in total dust deposition ranging from 10 to 50 (Morales-Baquero et al, 2006). A highly characteristic trait of the pelagic structure is an absence of autotrophic picoplankton Medina-Sánchez et al, 2002, 2004Carrillo et al, 2006;Delgado-Molina, in preparation). Dominant algae are Chrysophyceae (mainly Chromulina nevadensis) and Chlorophyceae (mainly Dyctiosphaerium chloralloides).…”
Section: Methodsmentioning
confidence: 99%
“…This ecosystem experiences frequent inputs of atmospheric Saharan dust containing high P levels, with a mean molar TN : TP ratio in total dust deposition ranging from 10 to 50 (Morales-Baquero et al, 2006). A highly characteristic trait of the pelagic structure is an absence of autotrophic picoplankton Medina-Sánchez et al, 2002, 2004Carrillo et al, 2006;Delgado-Molina, in preparation). Dominant algae are Chrysophyceae (mainly Chromulina nevadensis) and Chlorophyceae (mainly Dyctiosphaerium chloralloides).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that P-limited phytoplankton were often less resistant to UVR inhibitory effects (Doyle et al 2005). Medina-Sánchez et al (2002) also reported that UVB radiation inhibited bacteria when they were strongly P-deficient, whereas UVB exerted no direct effect on bacterial activity when they were not P-limited. A recent study showed that phosphorus amendment and UVR exposure had a synergistic negative effect on phytoplankton (Carrillo et al 2008).…”
Section: Factors Regulating Uvr Effectsmentioning
confidence: 96%
“…Intensity of fluorescence signal varied along with the sampled layer depth: low signal coinciding with low numbers of APP found, e.g., in August 2001, might reflect APP damage by UV radiation (Bertoni & Callieri 1999;Medina-Sánchez et al 2002). On the other hand, APP observed around the limit of the euphotic zone were much brighter, which could be connected with changes of photosynthetic pigment concentrations in low-light conditions (Callieri & Stockner 2002).…”
Section: Picoplankton Annual and Spatial Developmentmentioning
confidence: 98%
“…APP number-increase at the end of such blooms in surface waters could be explained as a result of succession / competition with these filamentous cyanobacteria (Callieri & Stockner 2002). Upon exhausted nutrients and possible UV inhibition in a high altitude lake (Bertoni & Callieri 1999;Medina-Sánchez et al 2002), the cyanobacteria rapidly died and settled down without an apparent effect on TPP development. Also Escobar et al (1999) showed that particulate biogenic carbon originated from Nodularia sp.…”
Section: Picoplankton Relation To Other Parametersmentioning
confidence: 99%